Expert Spring MVC and Web Flow - Yates, Colin; Ladd, Seth; Devijver, Steven; Davison, Darren (Apress : Imprint: Apress, 2006)
Expert Spring MVC and Web Flow provides in-depth coverage of Spring MVC and Spring Web Flow, two highly customizable and powerful web frameworks brought to you by the developers and community of the Spring Framework. Spring MVC is a modern web application framework built upon the Spring Framework, and Spring Web Flow is a new project that compliments Spring MVC for building reusable web controller modules that encapsulate rich page navigation rules. Along with detailed analysis of the code and functionality, plus the first-published coverage of Spring Web Flow, this book includes numerous tips and tricks to help you get the most out of Spring MVC, Spring Web Flow, and web development in general. Spring MVC and Spring Web Flow are engineered with an important consideration for design patterns and expert object oriented programming techniques. This book explains not only the design decisions of the frameworks, but also how you can apply similar designs and techniques to your own code. This book takes great care in covering every inch of Spring MVC and Spring Web Flow to give you the complete picture. Along with all the best known features of these frameworks, you'll discover some new hidden treasures. You'll also learn how to correctly and safely extend the frameworks to create customized solutions. From beginner to expert, this book is for anyone who wishes to write robust, modern, and useful web applications with the Spring Framework.